Conversioni al cattolicesimo a Roma tra Sei e Settecento. La presenza degli scandinavi nell’Ospizio dei Convertendi. - Raunio, Anu (fi=Turun yliopisto|en=University of Turku|, 2010)
In my PhD dissertation, I have examined a group of people of Scandinavian origin received by Ospizio dei Convertendi. This group has been hitherto largely unknown to historical research. The Ospizio was an institute founded by the Oratorian Congregation in Rome in 1673 to provide religious instruction and material aid to both recent and aspirant converts to Roman Catholicism. My research traces the profile of converts and a typology of motives, examining different factors which influenced the conversion process. I show that the key factors were often of a social rather than a religious nature. Moreover, I have analyzed the hospice in the context of Counter-Reformation charity as well. In terms of numbers, the Scandinavians formed a somewhat marginal yet not insignificant group within the Roman hospice. Out of a total of 2203 guests received between 1673 and 1706, 4.6 % were Scandinavians: 74 Swedes (including Finland and Livonia) and 27 Danes (including Norway). They came from a rigorously Protestant region which reacted to Catholicism with severe legislative measures. Converts to Catholicism risked confiscation of their goods, expulsion or even capital punishment. Since both Sweden and Denmark were practically impenetrable to Catholicism at the time and clandestine missionary attempts often failed before they had even properly started, the Roman Catholic Church shifted its interest towards Northerners arriving in Rome, a preferred destination for young noblemen, artists and migrant craftsmen. The material related to Ospizio dei Convertendi, conserved in the Vatican archives, is a scarcely known yet unusually rich source, not only for the religious history of our continent, but also for social history and the study of migration in early modern Europe. It contains a wealth of information about members of the subordinate classes, of their travels and lives in Europe. The profile delineated in these documents is of individuals who had a wide range of different professions and different aspirations. These documents encompass a vast social spectrum that was highly mobile on a continent which by that time had become pluriconfessional. Therefore, these migrants faced the complex religious reality in their everyday life. The principal corpus of my research consists of two types of manuscript sources created for administrative and in a way also for apologetic purposes of the Roman Catholic Church. My starting point is the Primo registro generale of Ospizio dei Convertendi. This is a volume in which the following information about each guest was registered: name, nationality, city of origin, age, sex, profession, confession professed before converting, date of arrival, departure, abjuration and baptism. Typically, the convert was male, originating from Stockholm or Copenhagen, from 21 to 30 years of age. The biggest occupational groups in descending order were soldiers, noblemen, craftsmen and sailors. Thus the data reflects a multiform reality of interurban and long distance migration, ideals regarding the education of young noblemen and gentry as well as the need of European armies to hire foreign mercenaries in their various campaigns. Against this background the almost total absence of women is hardly surprising: there is only one woman in the material I have studied. The second main source, Nota degl’ospiti ricevuti e spese fatte per essi, sheds more light on the choices of the converts, their motivations and their lives outside Scandinavia before reaching Rome. This narrative material permits an analysis which completes but also goes far beyond the columns of the Institute’s general register. This material consists of reports written by Catholic priests based on an interview conducted upon each guest’s arrival. The material frequently includes information on what the converts would do following their departure from the Institute as well. These sources have a specific narrative form and contain short biographies, list reasons for converting and information about the journey from the North to the Mediterranean - a journey which in many cases took several years. Moreover, they show that certain unorthodox practices such as calling on the saints and pleading for help from them were not uncommon in the Protestant popular religion. The recording of information on conversions from Protestantism to Catholicism reflects both religious and social interest on the part of the receiving institute. The information obtained was used for the purposes of religious teaching, for finding adequate ways of inserting the convert into Italian society so that he could earn a living, and to find effective methods to convert others with a similar cultural and geographical background. The stories recorded were based on interviews with the newly-arrived, information obtained from a travel companion or fellow countrymen, or from written documents the aspirant converts carried with them. These sources illustrate, although sometimes in rather simplified ways, the circumstances and motivations which were relevant to the choice of changing one’s confession. In addition, I have examined petitions addressed to the hospice and other Roman authorities in order to get financial aid. These petitions were written by Italian scrittori, and they contain certain conventions and topoi of presenting the conversion with the purpose of improving the chances of obtaining financial aid. It is through these filters, which may seem initially almost invisible, that the remote voice of the converts reaches us. The results of the analysis are particularly interesting because they disagree with some of the principal conclusions of previous work on the subject. First, earlier research has focused almost exclusively on the conversions of noblemen, and has argued, second, that the Queen Christina of Sweden was the driving force behind their change of confession. The sources examined for this dissertation present a profile of long-distance migrants, many of them members of the subordinate classes, who were looking for ways to make their living in Europe. These people had in many cases left their country of origin several years earlier and not for religious reasons, so, crucially, we are not dealing with confessional migration in these cases. Rather, conversion was a complex process, intricately tied up with strategies of survival, integration and upward social mobility. At the same time, while these components are significant on their own right, they do not necessarily point to the absence of motivations of a more clearly religious nature.

Väitöskirjatutkimuksen aiheena ovat katoliseen uskoon kääntyneet pohjoismaalaiset oratoriaanien vuonna 1673 Roomaan perustamassa hospitsissa, Ospizio dei Convertendissa. Pääasiallisena lähdemateriaalina on käytetty hospitsin rekisteriä sekä katolisten pappien käännynnäisten kertomusten pohjalta laatimia muistioita, jotka käsittelevät näiden elämänvaiheita ja kääntymysprosessia. Tutkimuksessa selvitetään käännynnäisten taustan lisäksi sitä, millaisia olivat ne olosuhteet ja syyt, jotka vaikuttivat eri tapauksissa tähän ratkaisuun. Tutkimuksessa luodataan lisäksi käännynnäisten myöhempiä vaiheita eri lähdesarjoja (erityisesti Pyhän Birgitan kongregaation ja Propaganda Fiden asiakirjat) yhdistämällä. Tavoitteena on monisyinen kokonaistulkinta menneisyyden yksilöistä uuden ajan alun Euroopan kulttuuri- ja kirkkohistoriallisessa kontekstissa. Ospizio dei Convertendissa oli tutkimuksessa käsiteltynä ajanjaksona (1673-1706) yhteensä 2203 vierasta, näistä osa, yhteensä 101 henkeä, kotoisin Ruotsista (Suomi ja Liivinmaa mukaan lukien) ja Tanskasta (Norja mukaan lukien). Toisin kuin aiemmissa tutkimuksissa on esitetty, katoliseen uskoon eivät kääntyneet vain aateliset tai oppineet. Käännynnäisten sosiaalinen kirjo on hyvin laaja: sotilaita, aatelisia, merimiehiä, taiteilijoita ja käsityöläisiä. Tarinoissa ei ole viitteitä uskonnollisesta siirtolaisuudesta, vaan niiden perusteella voidaan todeta, että kimmoke luterilaisen uskon hylkäämiseen tuli ulkomailla. Taustalla olivat usein käytännön syyt: moni oli elänyt useita vuosia Euroopan katolisilla alueilla ja saanut kimmokkeen luterilaisen uskon hylkäämiseen lähipiiristä, esimerkiksi mestarilta, perheenjäseneltä, katoliselta toverilta tai aviopuolisolta. Kertomuksissa esiintyy myös sairaana tai vankeudessa annettu lupaus matkasta Roomaan katolisen kirkon huomaan ahdingosta pelastumista tai sairaudesta parantumista vastaan. Pyhimyksiin vetoaminenkaan ei ole niissä harvinaista. Kertomukset osoittavat sen kuuluneen uuden ajan alun protestanttiseen kansankulttuuriin, jossa erilaiset, toisiinsa nähden ristiriitaisetkin, uskomukset ja käytännöt olivat läsnä. Katoliseen uskoon kääntymisen jälkeen useiden sotilaiden tiedetään taistelleen Morean sodassa tai sijoittuneen paavin vartiokaarteihin Roomassa. Lupaavimmat yksilöt koulutettiin lähetystyöhön Collegium Urbanumissa, joskin myöhemmin kävi ilmi, että tiukan lainsäädännön ja eri sääntökuntien ristiriitojen vuoksi lähetystyö Ruotsissa ja Tanskassa osoittautui käytännössä mahdottomaksi. Osa ruotsalaisista sijoittui kuningatar Kristiinan hoviin Palazzo Riarioon. Joidenkin osaksi lankesi köyhyys ja sen myötä Ospizio dei Convertendin tai Pyhän Birgitan kongregaation köyhäinapuun turvautuminen. Protestanttiseen kotimaahan saatettiin myöhemmin myös palata, eikä katolinen menneisyys 1600- ja 1700-lukujen vaihteessa estänyt edes valtiollisissa tai sotilasviroissa toimimista.